American Perspectives on Public Funding for Artists. Issue 6 (28th October 2021) - Novak-Leonard, Jennifer L.; Skaggs, Rachel
Abstract: In light of recent attention on artists as community assets, what is current U.S. public opinion on public support for artists? After tracing the history of perceptions of public funding of artists in the U.S., we turn to the contemporary moment. Using 2017 and 2019 data from novel national surveys of adults, this study examines opinions about whether artists should receive public funding. Logistic regression results reveal that historic demographic predictors of support for public arts funding also predict contemporary opinion about public funding for artists and, notably, that public opinion is significantly more supportive of public funding for artists when they are seen as collaborators, problem-solvers, and working to bring attention to community matters. These empirical results suggest new means for fostering and supporting artists' work in local communities.